Short message service prompts for skills practice in Internet‐delivered cognitive behaviour therapy for chronic pain – are they feasible and effective?. (13th April 2016) - Gandy, M.; Fogliati, V.J.; Terides, M.D.; Johnston, L.; Nicholson Perry, K.; Newall, C.; Titov, N.; Dear, B.F.
Abstract: Background: Patients face numerous challenges adopting skills taught within pain self‐management programmes. The present study reports the acceptability and preliminary outcomes of supplementing an Internet‐delivered cognitive behavioural therapy (iCBT) course for chronic pain, the Pain Course, with brief automated short message service (SMS) prompts that encourage skills practice. Methods: Participants were recruited from the Waitlist Control Group of a large randomized controlled trial and provided access to the Pain Course over 8 weeks, with the addition of SMS prompts. Fifteen SMS prompts were created to encourage the use of self‐management skills during the course. Participants were sent one random SMS prompt each business day. The acceptability of the SMS was assessed and clinical outcomes of participants who received prompts ( n  = 56) compared with a historical group who previously received the course without prompts ( n  = 139). Results: SMS prompts were rated highly with 85% reporting them to be very helpful or helpful and that they would recommend them to others. Clinical improvements for those receiving SMS, at post‐treatment and 3‐month follow‐up (disability, d  =   0.44; 0.58; anxiety d =  0.50; 0.51; depression, d  =   0.78; 0.79 and average pain d  =   0.49; 0.54), were consistent with participant who had received the course previously without SMS (ps >0.05). Conclusions: Brief automated SMS prompts were an acceptable adjunct to iCBT for chronic pain but did not result in any additional clinical benefit. Further research is needed to systematically evaluate the potential of SMS prompts to increase skills practice and facilitate treatment outcomes. What does this study add?: Automated short message service (SMS) messages are an acceptable means of prompting skills practice during iCBT for chronic pain. SMS prompts did not improve clinical outcomes of an established clinician‐supported iCBT programme.